Effect of Natural Zeolite (Clinoptilolite) on in vitro Biogenic Amine Production by Gram Positive and Gram Negative Pathogens - Özogul, Fatih; Šimat, Vida; Gokdogan, Saadet; Regenstein, Joe M.; Özogul, Yesim (Frontiers in Microbiology, 2018)
The effect of two levels of clinoptilolite (1 and 5%) on the production of biogenic amines (BA) and ammonia (AMN) by Gram positive (Staphylococcus aureus, Enterococcus faecalis and Listeria monocytogenes) and Gram negative bacteria (Aeromonas hydrophila, Klebsiella pneumoniae, Escherichia coli, Pseudomonas aeruginosa, Salmonella Parathypi A), in tyrosine decarboxylase broth (TDB) was studied. A. hydrophila and E. coli produced the highest amounts of amines which were 1223.06 and 2627.90 mg/l, respectively. All strains were able to decarboxylate tyrosine to tyramine (TYR) with E. coli being the highest (1657.19 mg/l). A. hydrophila formed >50 mg/l histamine (HIS) while the other strains produced none or very low concentrations (<4 mg/l). Among Gram-positive pathogens, E. faecalis was characterized as the main amine producer (478.23 mg/l). Although dependent on bacterial strain and level used, the natural zeolite clinoptilolite can be used to decrease BA and AMN production by bacterial strains that are of health concern.